A Graphite∥PTCDI Aqueous Dual‐Ion Battery. Issue 5 (8th February 2022) - Kim, Keun‐il; Tang, Longteng; Muratli, Jesse M.; Fang, Chong; Ji, Xiulei
Abstract: A full cell chemistry of aqueous dual‐ion battery (DIB) was reported, comprising the graphite cathode and 3, 4, 9, 10‐perylenetetracarboxylic diimide (PTCDI) as the anode. This DIB employed a mixture aqueous electrolyte: 5 m tributylmethylammonium (TBMA) chloride plus 5 m MgCl2, where [MgCl3 ] − and TBMA + serve as the charge carriers for cathode and anode of the DIB, respectively. This novel full cell exhibited a specific capacity of around 41 mAh g −1 based on the total active mass of both electrodes with an average operation voltage of 1.45 V and stable cycling for 400 cycles. Abstract : Energy storage : An aqueous concentrated electrolyte comprising 5 m MgCl2 and 5 m tributylmethylammonium chloride (TBMACl) is demonstrated to construct a graphite∥3, 4, 9, 10‐perylenetetracarboxylic diimide (PTCDI) full cell dual‐ion battery. The addition of TBMACl into saturated aqueous MgCl2 solution renders the formation of [MgCl3 ] −, which serves as an active charge carrier for the graphite cathode. Reversible storage of bulky TBMA + in the PTCDI anode is observed. A full cell delivers the initial reversible capacity of 41 mAh g −1 based on the mass of both electrodes and shows stable cycling over 400 cycles.